Development of an ethnomathematics-based E-LKPD on flat-sided solid geometry to enhance elementary students’ critical thinking skills - Rahayu, Salamah Tri; Nurhanurawati, Nurhanurawati; Rohman, Fatkhur; Adha, Mohammad Mona (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study aims to develop an ethnomathematics-based electronic student worksheet (e-LKPD) on flat shapes material that is valid, practical, and effective in improving the critical thinking skills of elementary school students. The integration of cultural elements into mathematics education is intended to make learning more meaningful and contextually relevant. Method: The research employed the Plomp development model, consisting of three phases: (1) preliminary investigation to identify learning needs and cultural relevance, (2) design and development of the e-LKPD incorporating ethnomathematical elements from the Lampung tapis cloth, and (3) evaluation of validity by experts, practicality by students, and effectiveness through pretest-posttest comparisons. Findings: The results of the study indicate that the developed ethnomathematics-based e-LKPD is highly valid, practical, and effective in supporting students' learning. Expert evaluations confirmed that the content, language, and media used in the e-LKPD met high standards of quality. Students found the material easy to use, engaging, and aligned with their learning needs. Moreover, the implementation of the e-LKPD led to a noticeable improvement in students’ critical thinking skills, as reflected in their increased ability to comprehend, analyze, and reflect on mathematical concepts presented through cultural contexts. Significance: This study contributes to the advancement of culturally responsive digital pedagogy in mathematics education. The ethnomathematics-based e-LKPD not only improves critical thinking but also fosters cultural appreciation and engagement. It serves as a replicable model for integrating local culture into digital learning tools and supports educational innovation aligned with 21st-century competencies.